Analisis Pengembangan Manajemen Perubahan Dalam Upaya Meningkatkan Efektivitas Penerapan Enterprise Resource Planning (Studi Kasus Pada PTPN IV Ajamu 3 Panai Jaya) - Melati, Melati; Aslami, Nuri (LPPM Universitas Labuhanbatu, 2022)
Enterprise Resource Planning (ERP) is concerned with the business activities of a substantial and complex system organization. Unlike other information systems implementation projects, ERP system implementation projects are unique. The scale, complexity, organizational impact, expenses associated with this project, and other effects that will result from project failure are some of the key differences. The findings of this study are expected to be taken into consideration for change management strategies that can have an impact on the effectiveness of ERP installations at the PTPN IV AJAMU 3panai jaya Finance Directorate. To anticipate the performance of the ERP system implementation program, the DICE framework and change management models are used as study references by scholars. The DICE framework can measure programmatic external manifestations, such as longevity, implementer honesty, and leadership and staff commitment. This study uses qualitative methods and gathers information through in-depth interviews and focus groups with workers who make up the main ERP implementation team. managed and understood effectively. Therefore, a company's competitiveness will increase if it manages change better, which will help it survive and maintain its effectiveness through change strategies and programs.